Estimating the length of the first antiretroviral therapy regiment durability in São Paulo, Brazil - Roseane Medeiros (Brazilian Journal of Infectious Diseases)
Brazil was the first country to provide unrestricted, cost-free access to antiretroviral (ARV) medicine for AIDS treatment. However, there is little data about the benefits of such a policy for these patients. We evaluated the duration of benefit obtained with the introduction of ARVs, defined as the durability of the first ARV regiment. We reviewed the medical charts of patients attended from 1996-2000, at the outpatient clinics of the Federal University of São Paulo, Brazil. A total of 120 drug-naive HIV-1 infected patients were eligible to participate in the study. About half of the individuals (53%) presented with disease symptoms; 59% of them had CD4 count below 200 cells/mm³. Mean estimated duration of the benefit of therapy was 14.1 months. The most used regimen in this cohort was Zidovudine/3TC/Indinavir (26%), followed by Zidovudine/DDI (17%), and Zidovudine/3TC/Nelfinavir (13%). The most frequent cause of interruption of therapy was gastrointestinal intolerance. Use of treatment regimens with three drugs was more effective than with two drugs, but only for patients with CD4<200 cells/mm³ or CV>100,000 copies RNA/mL. However, the use of triple therapy was associated with a significantly higher probability of reaching maximum viral suppression, during a longer period (p<0.05).The patients enrolled in the study benefitted from therapy for a limited time, after the introduction of double or triple antiretroviral therapy. The incidence of adverse events was significantly associated with loss of the benefits provided by the initial therapeutic regimen.